EFEKTIVITAS MODEL PEMBELAJARAN INKUIRI TERBIMBING PADA PEMBELAJARAN FISIKA SISWA KELAS VII SMP IT ANNAJIYAH - Wandira, Ayu; Gumay, Ovilia Putri Utami (Karst: Jurnal Pendidikan Fisika dan Terapannya, 2024)
The Effectiveness of the Guided Inquiry Learning Model in Physics Learning for Grade VII Students of SMP IT Annajiyah. This study explores the effectiveness of the guided inquiry model in teaching physics to seventh-grade students at SMP IT Annajiyah. It employs a qualitative approach with descriptive methods and a quasi-experimental design. The participants were students engaging in physics lessons using the guided inquiry approach. Data were collected through classroom observations to assess student participation, conceptual understanding, and responses to the learning process. The guided inquiry model was designed to actively involve students in exploration, investigation, and problem-solving under teacher guidance. The findings indicate that this approach enhances students' interest, participation, and engagement in learning activities. Thus, the guided inquiry model is an effective method for teaching physics at the middle school level.